The Effectiveness of Audio Storytelling in Improving Students’ Listening Skills in EFL Classrooms - Sitti Aisa; Sam Hermansyah; Isumarni; Nurul Faradillah; Nur Hikmah (Universitas Islam Negeri Palopo, 2025)
Listening comprehension plays a crucial role in tertiary EFL learning; however, many university students struggle due to limited exposure to contextualized and authentic audio input. Despite the growing use of storytelling in language teaching, few empirical studies have examined the effectiveness of audio-only storytelling in higher education EFL listening classrooms. This study investigates whether audio storytelling significantly improves university students’ listening comprehension. A quasi-experimental one-group pre-test–post-test design was employed involving 30 undergraduate EFL students selected through purposive sampling. Data were collected using a validated listening comprehension test and analyzed through descriptive statistics and a paired-sample t-test. The results showed a significant improvement in students’ mean scores from 62.40 (pre-test) to 78.60 (post-test), with p < 0.05. The calculated effect size indicated a strong practical impact. These findings suggest that audio storytelling provides contextualized and meaningful input that significantly enhances listening comprehension in tertiary EFL classrooms.